2
$\begingroup$

We are trying to solve an assignment where we have to simplify a logical statement. Can anyone explain what is going on this step? $$(\neg P\lor \neg Q)\land (\neg P\lor Q) \equiv \neg P\lor(\neg Q\land Q)$$

How do we get from $(\neg P\lor \neg Q)\land(\neg P \lor Q)$ to $\neg P\lor(\neg Q\land Q)$? What simplification rule is being used here?

$\endgroup$
1
$\begingroup$

This follows from the Distributive law.

We have $$(P\land (Q\lor R)) \equiv (P\land Q)\lor (P\land R)$$ $$(P\lor (Q\land R)) \equiv (P\lor Q)\land (P\lor R)$$

$\endgroup$
1
$\begingroup$

This is distributivity of disjunction over conjunction: $A \vee (B \wedge C)$ is equivalent to $(A \vee B) \wedge (A \vee C)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.